2008
DOI: 10.1291/hypres.31.2129
|View full text |Cite
|
Sign up to set email alerts
|

Masked Hypertension Determined by Self-Measured Blood Pressure at Home and Chronic Kidney Disease in the Japanese General Population: The Ohasama Study

Abstract: , Takayoshi OHKUBO 4), 5) , Masahiro KIKUYA 6) , Kei ASAYAMA 4), 5) , Ryusuke INOUE 5) , Haruhisa HOSHI 7) , Sadayoshi ITO 1) , and Yutaka IMAI 59.6 mL/min, and 57.3 mL/min for CCr, 4.2%, 8.9%, 10.3%, and 12.8% for the prevalence of positive proteinuria, and 2.3%, 3.0%, 6.3%, and 9.8% for the proportion with CCr <60 mL/min with proteinuria. Compared with the SNBP group, the MHT and SHT groups exhibited significant differences in these parameters (p <0.05, for each). The adjusted odds ratios for CCr … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 26 publications
3
21
0
1
Order By: Relevance
“…7 We have also previously reported that MHT on the basis of HBP is significantly associated with creatinine clearance o60 ml min À1 with proteinuria when compared with SNBP in the general population. 13 Consistent with those findings, this study demonstrated that individuals with MHT on the basis of ABP showed a higher prevalence of proteinuria, eGFR o60 ml min À1 per 1.73 m 2 and CKD.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…7 We have also previously reported that MHT on the basis of HBP is significantly associated with creatinine clearance o60 ml min À1 with proteinuria when compared with SNBP in the general population. 13 Consistent with those findings, this study demonstrated that individuals with MHT on the basis of ABP showed a higher prevalence of proteinuria, eGFR o60 ml min À1 per 1.73 m 2 and CKD.…”
Section: Discussionsupporting
confidence: 90%
“…13 Of the 2013 residents who participated in checkups from 1992 to 1997, data on serum creatinine levels, dipstick test for spot urine and confounding factors were unavailable for 214 subjects. Of the remaining 1799 individuals, ABP measurements were recorded in 1073 participants.…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…In the general population, the risk of chronic kidney disease has been reported to be high in patients with masked hypertension, as determined by home BP measurements. 148 In patients undergoing dialysis, the greatest prognostic factor is the presence of cerebroand cardiovascular complications, and the management of hypertension is extremely important. However, BP measured at the dialysis center fluctuates widely, and has been reported to not accurately reflect the outcome.…”
Section: Pregnancymentioning
confidence: 99%
“…Several reports have shown that BP measured at home has superior predictive value for mortality, cardiovascular events 6 and stroke, 7,8 and screening value for asymptomatic cerebral ischemia 9 and CKD. 10 In addition, a previous study showed that home-measured BP is better than clinicmeasured BP at predicting the progression of disease in 'general' CKD patients. 11 In an article appearing in this issue, Okada et al 12 used home BP monitoring, and assessed the prognostic value of home BP (morning and evening) and casual BP for renal and cardiovascular outcome in elderly CKD patients (age X70 years).…”
mentioning
confidence: 99%